Improved scaling of spectrum decision mechanism in cognitive radio networks - Peng Yi; Hou Yong Ji; Long Hua; Li Hai Tao (Institute of Advanced Engineering and Science, 2014)
In cognitive radio networks,We usually use nine scaling law based on multi-attribute utility theory as a common spectrum decision mechanism.the traditional scale method only consider the spectrum own objective properties and then makes judgments is not comprehensive enough. This paper through researched the mechanism of scaling judgment in psychology, a new and improved scale method were proposed, and the new scale method applied to spectrum decisions ofcognitive radio networks, So that the measure of subjective judgment factors are more scientific and makes more explicit determination in spectrum decisions. Finally through calculate consistency index to verify the superiority of the improved scaling.